ANALISIS DETERMINAN PERTUMBUHAN EKONOMI SUMATERA SELATAN - Nazipawati Nazipawati; Novegya Ratih Primanda; Novie Al Muhariah; Ali Akbar (Universitas Sang Bumi Ruwa Jurai, 2023)
The purpose of this study was to ascertain how South Sumatra Province's economic growth would be impacted by labor availability and road infrastructure between 2002 and 2020. This study used multiple linear regression analysis as a quantitative research technique. The study's data sources came from the Central Statistics Agency (BPS) and the Public Works Service, and the data used were secondary data (time series) for a period of 19 years (2002-2020). (Bina Marga). According to the study's findings, the number of workers and the state of the roads had a major impact on economic growth in the province of South Sumatera between 2002 and 2020. The number of workers and the state of the roads are the independent factors in this study, whereas economic growth is the dependent variable. This research can be used as guidance for the regional government of South Sumatra Province to increase new employment opportunities to help absorb labor and also support central government policies in an effort to absorb labor, for example, the acquisition of pre-employment card programs and the implementation of pre-employment card programs.